2003
DOI: 10.1159/000072906
|View full text |Cite
|
Sign up to set email alerts
|

Fluorodeoxyglucose PET Scan in Pulmonary Sarcoidosis during Treatment with Inhaled and Oral Corticosteroids

Abstract: The objective was to investigate longitudinal changes in fluorodeoxyglucose PET scan (FDG-PET) in a patient with pulmonary sarcoidosis prior to and during treatment with inhaled corticosteroids followed by systemic corticosteroids. The patient was a 41-year-old man presenting with stage I pulmonary sarcoidosis (hilar adenopathy), which had progressed to stage II (pulmonary infiltrates) 19 months later. FDG-PET was performed at 19, 29 and 33 months after presentation. No treatment was given prior to the 1st PET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 9 publications
2
10
0
2
Order By: Relevance
“…The SUVmax values of the mediastinum in patients with currently diagnosed and relapsed stage 1 sarcoidosis were higher than those in patients with stage 2 sarcoidosis (p = 0.003). Also, Milman et al [20] showed a significant decrease in the FDG uptake in the hilum and mediastinum and an unchanged or slightly increased uptake in the lung parenchyma following treatment with inhaled corticosteroids, consistent with a shift from stage 1 to stage 2 disease, as in our study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The SUVmax values of the mediastinum in patients with currently diagnosed and relapsed stage 1 sarcoidosis were higher than those in patients with stage 2 sarcoidosis (p = 0.003). Also, Milman et al [20] showed a significant decrease in the FDG uptake in the hilum and mediastinum and an unchanged or slightly increased uptake in the lung parenchyma following treatment with inhaled corticosteroids, consistent with a shift from stage 1 to stage 2 disease, as in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, when Braun et al [8] treated five patients with corticosteroids, complete regression occurred in two patients, improvement but incomplete regression occurred in another two, and disease progression occurred in the fifth patient. Some case reports have also demonstrated the efficacy of corticosteroid treatment as evidenced by FDG PET [20,21,23].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These areas of increased metabolic activity resolved with appropriate therapy while corresponding CT abnormalities persisted [40]. Similar utility has been reported in cases of sarcoidosis [41]. …”
Section: Other Potential Uses For 18f-fdg-pet/pet-ctsupporting
confidence: 58%
“…Several published case reports and small case series indicate the usefulness of 18 F-FDG PET and 18 F-FDG PET/CT for monitoring the effect of therapy in patients with sarcoidosis (19,(32)(33)(34). To our best knowledge, however, this was the first prospective study to specifically address the association between 18 F-FDG PET/CT results and subsequent patient management.…”
Section: Discussionmentioning
confidence: 99%